The Effectiveness of Training Program Based on TRIZ Theory to Develop the Creative Thinking Skills for the Teachers of king Abdullah ll Schools for Excellence in Jordan - Al-Sheyyab, Alaa Yousef; Shnekat, Feryal Abd Al-Hadi (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the effectiveness of a training program based on the Therese theory to develop creative thinking skills for teachers of King Abdullah II Schools of Excellence in Jordan. The study sample consisted of (40) teachers from teachers of King Abdullah II schools for excellence in Al Balqa governorate and Madaba Governorate, In the second semester of the year 2018/2019, and they were chosen intentionally from the study community. They were divided into two groups: the control group by (20) male and female teachers from the schools of King Abdullah II for Excellence in the Madaba governorate who were not subjected to treatment. The experimental group of (20) male and female teachers of King Abdullah II Schools of Excellence in Al Balqa governorate underwent the training program, and the researcher prepared a training program based on the theory of promotion to develop creative thinking skills. The Torrance test was used for creative thinking - the words "A"The study reached the following results: • There were statistically significant differences between the averages of the performance of the post-study members on the test of creative thinking skills, total and sub-due to the group variable (experimental, control), where the differences were in favor of the experimental group. The absence of statistically significant differences between the averages of the performance of the post-study individuals on the test of creative thinking skills, college and sub, due to the variable of the academic qualification and specialization and the interaction between the group variables and the academic qualification and specialization. The study recommended conducting studies to compare programs based on the Therese theory with programs based on other theories to see whether developing creative thinking skills among teachers improves their teaching methods for gifted students.